Assigning Electronic States in Carbon Nanodots. (13th September 2016) - Strauss, Volker; Kahnt, Axel; Zolnhofer, Eva M.; Meyer, Karsten; Maid, Harald; Placht, Christian; Bauer, Walter; Nacken, Thomas J.; Peukert, Wolfgang; Etschel, Sebastian H.; Halik, Marcus; Guldi, Dirk M.
Abstract : Luminescent carbon nanodots exhibit enormous potential to be used as functional building blocks in energy conversion devices. Their intrinsic heterogeneity, however, hinders a thorough characterization and subsequently their applicability. In this work, the spectroscopic and electrochemical properties of prototype carbon nanodots were thoroughly studied in solution. Spectro‐electrochemical experiments revealed information on the spectral features of several oxidized and reduced species of our carbon nanodots. Therefore, these experiments were complemented with pulse radiolysis where the spectral signature of the one‐electron oxidized and reduced forms were identified. Both, electrochemically and radiolytically reduced and oxidized products show high reactivity in solution which correlates with an open‐shell character, detected by paramagnetic resonance spectroscopy. The herein presented studies help to understand the complex nature of carbon nanodots and serve to overcome difficulties in device fabrication. Abstract : The electrochemical properties and the response of the spectral features toward electrical potentials of prototype carbon nanodots are investigated. Open‐shell character and high reactivity of the products are evident from electron paramagnetic resonance spectroscopy and pulse radiolytic experiments.